UPAYA PENINGKATAN HASIL BELAJAR SISWA DENGAN METODE EKSPERIMEN PADA PEMBELAJARAN IPA KELAS 5A SDN 01 TAMAN KOTA MADIUN TAHUN AJARAN 2023/2024 - Rahayu, Sri; Tryanasari, Dewi; Jatmikawati, Melina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to improve the learning outcomes of class VA students in science learning at SD Negeri 1 Taman Kota Madiun using experimental methods. This research is classroom action research. This research was carried out at SDN 01 Taman Kota Madiun in semester 2 of the 2023/2024 academic year. The research subjects were 18 VA class students. The research objects were analyzed descriptively qualitatively and quantitatively. The research results show that using experimental methods improves student learning outcomes. This can be seen from the learning results of 18 students who had an average in the pre-cycle of 64.44, while cycle 1 experienced an increase to 74.44 and cycle 2 experienced an increase again to 81.66.